A review of the geckos of the genus Hemidactylus (Squamata: Gekkonidae) from Oman based on morphology, mitochondrial and nuclear data, with descriptions of eight new species - Carranza, Salvador; Arnold, Edwin Nicholas (Zootaxa, 2012)
The genus Hemidactylus is one of the most species-rich and widely distributed of all reptile genera, being found in thetropical and subtropical regions of the world and hundreds of continental and oceanic islands. Despite having already 111species, the number of species described in recent years is very high. This has been facilitated, in part, by the use ofmolecular techniques, which in most cases have been employed to confirm the differentiation at the DNA level of somemorphologically variable forms and to discover some cryptic lineages.Preliminary analyses indicate that some Hemidactylus species from Oman are quite variable in their morphologyand may include more than one species. In order to test this hypothesis we inferred a molecular phylogeny including 131Hemidactylus (20 species) using 1385 base pairs of mitochondrial DNA (353 bp 12S; 302 bp cytb; 588 bp nd4 and 142bp tRNAs) and 1481 bp of nuclear DNA (403 bp c-mos; 668 bp mc1r and 410 bp rag2) and analyzed 226 specimens (15species) for several meristic and pholidotic characters of which we took 3103 photographs that have been deposited inMorphoBank (project 483). Our results indicate the presence of eight new species of Hemidactylus geckos in Arabia: H.luqueorum sp. nov. and H. hajarensis sp. nov. from North Oman; H. masirahensis sp. nov. from Masirah Island; H.inexpectatus sp. nov. from one locality on coastal Central Oman; H. alkiyumii sp. nov., H. festivus sp. nov. and H.paucituberculatus sp. nov. from Dhofar, Southern Oman; and finally H. endophis sp. nov. probably from North Omanand described on the basis of morphology alone. An identification key to the genus Hemidactylus from Oman is alsopresented. With these descriptions, the number of Hemidactylus species found in Oman increases from 7 to 13 and thenumber of endemic Hemidactylus from 0 to 6. The description of three new species endemic to the Hajar Mountains inNorth Oman highlights the importance of this mountain range as a biodiversity hotspot that, up to now, includes 12reptile species that are found nowhere else in the World. Another hotspot of Hemidactylus biodiversity is the DhofarMountain range, in the extreme Southwestern corner of Oman and East Yemen. As a result of its particular geographicsituation, orography and the effect of the Southwest Monsoons, this mountain range presents a diverse variety of habitatswith different species of Hemidactylus adapted to them.With the exception of H. flaviviridis and H. leschenaultii, which belong to the Tropical Asian clade of Hemidactylus,all Arabian Hemidactylus for which DNA sequence is available are members of the Arid clade of Hemidactylus.Relatively recent dispersal appears to have taken place within Arabia in the H. turcicus group, with the South Arabian H.lemurinus occurring far from other confirmed members of this assemblage. Hemidactylus flaviviridis and a clade of H. robustus are genetically uniform, widespread in Arabia and beyond and occur around human habitations, suggesting thatmuch of their large distributions are anthropogenic, as appears to be so in several other Hemidactylus species outsideArabia.The way in which species of Arabian Hemidactylus separate ecologically is surprisingly varied. They may occur atsimilar altitudes but replace each other geographically, or if they are sympatric there may be altitudinal separation.Humidity may also be an important factor, and when animals exist within a few meters of each other, structural nichemay be significant. While four native species occur close together in Dhofar, most Hemidactylus communities in Arabiaconsist of only one or two species, although climbing geckos belonging to other genera, such as Asaccus and Ptyodactylus, may also be present.‫غ‬